2011
DOI: 10.1177/2040622311426204
|View full text |Cite
|
Sign up to set email alerts
|

Indacaterol in chronic obstructive pulmonary disease: an update for clinicians

Abstract: Bronchodilation is the cornerstone of chronic obstructive pulmonary disease (COPD) management and is based on regular treatment with one or more long-acting b 2 agonists (LABAs). A novel bronchodilator, indacaterol, satisfies the requirements of an efficacious LABA: it has a relatively longer duration of action compared with existing LABAs and a fast onset of action. This review is a presentation of data on indacaterol with respect to its molecular characteristics as well as comparisons with other long-acting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Indacaterol is a once-daily, inhaled, ultra-long-acting ADRB2 agonist recently approved by FDA for the management of patients with COPD ( Donohue et al, 2010 ). Furthermore, growing body of evidence indicates that indacaterol is statistically superior to twice-daily LABAs (salmeterol and formoterol) and once-daily anticholinergic tiotropium in COPD patients with dyspnea ( Yorgancioglu, 2012 ). While indacaterol is an important therapeutic agent for symptom relief in COPD patients, the molecular mechanism of its pharmacological action remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Indacaterol is a once-daily, inhaled, ultra-long-acting ADRB2 agonist recently approved by FDA for the management of patients with COPD ( Donohue et al, 2010 ). Furthermore, growing body of evidence indicates that indacaterol is statistically superior to twice-daily LABAs (salmeterol and formoterol) and once-daily anticholinergic tiotropium in COPD patients with dyspnea ( Yorgancioglu, 2012 ). While indacaterol is an important therapeutic agent for symptom relief in COPD patients, the molecular mechanism of its pharmacological action remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…To further con rm the speci c β2AR effect and to compare the natural agonist to a medically used agonist, we used the β2 sympathomimetic indacaterol. Indacaterol is a LABA and it is proposed to dissociate slower from the membrane, to stay in close proximity to the β2AR and to continuously stimulate the receptor 56,57 . Like epinephrine, treatment with indacaterol signi cantly decreased LFA-1 activity, which was also reversible by propranolol (Fig.…”
Section: β2 Agonists Block Lfa-1 Activity and Cytotoxicity Of Nk Cellsmentioning
confidence: 99%
“…Several randomized studies performed in patients with moderate-to-severe COPD have shown that indacaterol improved the symptoms, lung function, and quality of life; reduced the use of rescue medications; and was well tolerated with an acceptable safety profile ( 9 - 13 ). The efficacy and safety of indacaterol have also been evaluated in Asian populations, including those in Japan ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%